Design and Construction of An IoT-Based Automatic Wood Cutting Calculation System on A Table Saw - Putra, Yufran; Arisandi, Riyan; Muchtar, Masjono; Tri Budi Utami, Atikah (UPPM Poltek ATI Makassar, 2025)
Precise wood cutting is essential in the woodworking industry to maintain product quality and optimize raw material usage. This study aimed to design and implement an automatic wood cutting counter system based on the Internet of Things (IoT) for a table saw machine. The system utilized a TCRT5000 infrared sensor to detect cut pieces, an ESP32 microcontroller as the data processor, and the Blynk platform for smartphone-based monitoring. The design process was divided into two main stages: hardware assembly and software development using the Arduino IDE. The system was tested by comparing its counting results to manual calculations. The test results indicated that the system successfully counted wood pieces and displayed real-time data through the Blynk application. This automated system reduced human error in production monitoring and supported the digitalization of woodworking processes. The findings suggest that this approach can improve production efficiency, provide affordable implementation in small to medium-scale industries, and serve as a reference for further IoT applications in woodworking environments.Keyword:Table Saw; TCRT5000; IoT; ESP32; Blynk